STUDI PENGEMBANGAN EKOWISATA MELALUI PENDEKATAN SUPPLY DAN DEMAND DI TAHURA SULTAN SYARIF HASYIM RIAU - Indrayati '; Defri Yoza; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Tahura Sultan Syarif Hasyim is one of the forest region in Riau which can be developed as an ecotourism object. The devolopment of ecotourism needs the integration supply and demand aspects. The object of research was to identify the supply and demand aspects an also to find out the strategy in developing Tahura Sultan Syarif Hasyim. The technique of collecting data used by the researcher was using questionnaire, observation, and literature review. The technique of analyzing data was using scoring analysis, descriptive analysis, and SWOT analysis. The result of this research was Tahura Sultan Syarif Hasyim has the supply aspects which consist of natural resources, facility and infrastructure, accessibility an local society, whereas the demand aspects consist of characteristics, motivation, perception, and expectation of the visitors. Some strategies which can be applied in developing ecotourism for instance through developing the nature tourism by adding the supporting facility and infrastructure, empowering the local society around tahura, promoting Tahura Sultan Syarif Hasyim in various types of advertisement, improving the facility and infrastructure which have existed. Keyword : Supply, Demand, Ecotourism, Tahura